Isolation Room Design: Indoor Environmental Quality, Theoretical Perspectives, and Future Considerations - Ahmad, Khrisna Prasadya Farras; Ismail, Iziq Eafifi Bin; Zakaria, Adila Binti (Jurnal Syntax Transformation, 2025)
Isolation rooms are critical healthcare facilities designed to contain infectious respiratory diseases through negative-pressure systems and environmental controls. In Indonesia, their design is guided by the Pedoman Teknis Ruang Isolasi (2014), which outlines standards for ventilation, lighting, acoustics, thermal comfort, and air quality. However, these regulations primarily emphasise infection control, with limited consideration of patients’ psychological and social well-being. This study aims to review Indonesian isolation room standards and evaluate them through the lens of Indoor Environmental Quality (IEQ) and environmental psychology theories, including the healing environment framework, Canter’s place theory, and person–environment fit. A Post-Occupancy Evaluation (POE) approach is proposed as the methodological bridge between regulatory compliance and patient experience. The findings indicate that while current standards ensure functional safety, they lack integration with patient-centred design elements that contribute to comfort, resilience, and recovery. The paper highlights the potential of incorporating smart technologies and adaptive systems to enhance flexibility and psychosocial support. These insights have significant implications for interdisciplinary collaboration in revising future standards, ensuring that isolation rooms not only safeguard against infection but also foster environments conducive to healing and well-being.